(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2017)
This study aimed at determining (1) leadership of headmasterâ€™s Vocational School of PGRI Tanjung Raja as academic supervisor; (2) the teachersâ€™ performance of Vocational School of PGRI Tanjung Raja; and (3) the influence of headmaster’s leadership on the teachersâ€™ performance of Vocational School of PGRI Tanjung Raja. This research was quantitative research with expostfacto approach. The population in this study were the teachers of Vocational School PGRI Tanjung Raja consist of 85 teachers and then the sample was 60 teachers which selected by area proportional random sampling technique. The data collection instrument was questionnaire with Likert scale which has 4 alternative answers, on 100 items. The data analysis was used simple regression analysis technique. The results showed (1) leadership of headmasterâ€™s Vocational School of PGRI Tanjung Raja according to some teachers (52%) high category; then (2) the teachersâ€™ performance of Vocational School PGRI Tanjung Raja (52%) high category; and (3) there is a positive and significant influence of headmaster leadership as academic supervisor on teachersâ€™ performance 65,1% happened to teacherâ€™s performance can be explained by headmaster leadership as academic supervisor, while 80,7% other explained by other variable not included in this study such as teacherâ€™s knowledge, teachersâ€™ personality, dedication, professional development, and so forth. Kata Kunci: Headmasterâ€™s Leadership, Teachersâ€™ Performance, Vocational School PGRI Tanjung Raja